If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5a + 6 = a + -38 Reorder the terms: 6 + -5a = a + -38 Reorder the terms: 6 + -5a = -38 + a Solving 6 + -5a = -38 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 6 + -5a + -1a = -38 + a + -1a Combine like terms: -5a + -1a = -6a 6 + -6a = -38 + a + -1a Combine like terms: a + -1a = 0 6 + -6a = -38 + 0 6 + -6a = -38 Add '-6' to each side of the equation. 6 + -6 + -6a = -38 + -6 Combine like terms: 6 + -6 = 0 0 + -6a = -38 + -6 -6a = -38 + -6 Combine like terms: -38 + -6 = -44 -6a = -44 Divide each side by '-6'. a = 7.333333333 Simplifying a = 7.333333333
| 5=-4x-7 | | 4k=48 | | 0.5x+4-x=2.5+x | | 2=5x+4(-4x) | | k-3=9 | | -(5v-8)=-2(v+5) | | 5y+5=7+y | | 1-4=x-3+2(2) | | 5m+7=62 | | 1=-5y-(9y+3) | | 3x^2+4x=2x+3 | | y=x+9+3 | | 4x-0.5+6x=5-x | | -3x=1+2(2) | | (5x-4)(2x-9)= | | (2x^2)-5x-12=0 | | 9b+12(b+12)=-12(b-1) | | y=(x-3)2+3 | | (4x+3)(5x+8)= | | 5b-4=21 | | 8(3x-4)=4(6x+6) | | x^2+5x=3x-11 | | -(6n+2)=-(-3-7n)-2n | | 5(x-3)+4(x+2)=13-2x | | 7(5-5)=42 | | 5-x=21 | | -5(1+n)=-2(10+10n) | | (2u-9)(1+u)=0 | | -x^2+4x=2x^2+3 | | 1.5x+2=8+x | | (x-9)(x-1)= | | -7=3(5x)+4x |